Photon-Energy-Dependent Reversible Charge Transfer Dynamics of Double Perovskite Nanocrystal-Polymer Nanocomposites - Ruixiang Wu; Xiaoshuai Wang; Jingjing Luo; Xin Liu; Fengjie Guo; Bin Li; Shengzhi Wang; Peigeng Han; Xiangyang Miao (Nanomaterials, 2022)
Combining steady-state photoluminescence and transient absorption (TA) spectroscopy, we have investigated the photoinduced charge transfer dynamics between lead-free Mn-doped Cs2NaIn0.75Bi0.25Cl6 double perovskite (DP) nanocrystals (NCs) and conjugated poly[2-methoxy-5-(3′,7′-dimethyloctyloxy)-1,4-phenylenevinylene] (MDMO-PPV). Upon ultraviolet-A excitation, the photoinduced absorption feature of DP NCs/MDMO-PPV nanocomposites disappeared, and the stimulated emission weakened in the TA spectrum. This was due to charge transfer from the MDMO-PPV polymers to DP NCs. Upon a higher photon-energy ultraviolet-C excitation, stimulated emission and photoinduced absorption features vanished, indicating there existed a reversible charge transfer from DP NCs to MDMO-PPV polymers. Reversible charge transfer of Mn-doped DP NCs/MDMO-PPV nanocomposites was tuned by varying the excitation photon-energy. The manipulation of reversible charge transfer dynamics in the perovskite-polymer nanocomposites opens a new avenue for optical and optoelectronic applications.